Porphyromonas gingivalis, a bridge between oral health and immune evasion in gastric cancer - Muñoz-Medel, Matías; Pinto, Mauricio P.; Goralsky, Lauren; Cáceres, Mónica; Villarroel-Espíndola, Franz; Manque, Patricio; Pinto, Andrés; Garcia-Bloj, Benjamin; de Mayo, Tomas; Godoy, Juan A.; Garrido, Marcelo; Retamal, Ignacio N. (Frontiers in Oncology, 2024)
Porphyromonas gingivalis (P. gingivalis) is a gram-negative oral pathogen associated with chronic periodontitis. Previous studies have linked poor oral health and periodontitis with oral cancer. Severe cases of periodontal disease can result in advanced periodontitis, leading to tissue degradation, tooth loss, and may also correlate with higher gastric cancer (GC) risk. In fact, tooth loss is associated with an elevated risk of cancer. However, the clinical evidence for this association remains inconclusive. Periodontitis is also characterized by chronic inflammation and upregulation of members of the Programmed Death 1/PD1 Ligand 1 (PD1/PDL1) axis that leads to an immunosuppressive state. Given that chronic inflammation and immunosuppression are conditions that facilitate cancer progression and carcinogenesis, we hypothesize that oral P. gingivalis and/or its virulence factors serve as a mechanistic link between oral health and gastric carcinogenesis/GC progression. We also discuss the potential impact of P. gingivalis' virulence factors (gingipains, lipopolysaccharide (LPS), and fimbriae) on inflammation and the response to immune checkpoint inhibitors in GC which are part of the current standard of care for advanced stage patients.